2020
DOI: 10.1097/cce.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-Event Simulation Modeling of Critical Care Flow: New Hospital, Old Challenges

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…There was only one paper with research conducted on how systems would manage if a sudden rise in frail and elderly patients were to occur [6]. Sudden increase in demand is not a novel area to healthcare modelling with a high quantity of papers investigating this issue, e.g., intensive care units [17,44,79].…”
Section: Discussionmentioning
confidence: 99%
“…There was only one paper with research conducted on how systems would manage if a sudden rise in frail and elderly patients were to occur [6]. Sudden increase in demand is not a novel area to healthcare modelling with a high quantity of papers investigating this issue, e.g., intensive care units [17,44,79].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the modelling of business processes, a sequence of events (activities), is discrete event modelling. (Williams, Szakmany, Spernaes, Muthuswamy & Holborn, 2020) applied DES in analyzing the impact of various scenarios on critical care bed occupancy. (Hajrizi & Berisha, 2019) applied DES and multi-objective optimization simulation to reduce the length of stay and waiting times at an emergency department.…”
Section: Business Processes and Discrete Event Modellingmentioning
confidence: 99%
“…In addition to reduction in mortality, the Randomised, Embedded, Multi-factorial, Adaptive Platform Trial for Community-Acquired Pneumonia (REMAP-CAP) trial has found significant reduction in organ support needs and reduction in length of ICU stay in the IL-6 receptor blockade arms, while the RECOVERY trial reported significantly less progression to mechanical ventilation or death in those patients who only needed supplemental oxygen on randomization ( 6 , 12 ). This is especially important as these data could inform further modeling of healthcare resource needs during the pandemic, where stretched ICU capacity has been linked to adverse outcomes ( 13 , 14 ).…”
Section: To the Editormentioning
confidence: 99%